Value Stream Mapping for Warehouse Process in Automotive Manufacturing Case - Maryadi, Deri; Moulita, R.A Nurul; Luther King, Marthin; Maria Veranika, Rita; Madagaskar, Madagaskar (International Journal of Mechanical Computational and Manufacturing Research, 2024)
KD parts warehouse is a transit and connection place before the KD parts (Knock Down) car’s body and material from Automotive manufacturing, to export destination in several countries or destination. The faster the warehouse operation process will make the company's export performance better. This research aims to reduce NVA and NNVA activities' concern in warehouse KD operations in Japanese automotive manufacturers in Cikarang. The application of lean thinking with the VSM (Value Stream Mapping) approach eliminates the waste of activities and processes in the KD warehouse. From the CVSM and PMA (Process Mapping Analysis) results, the work efficiency is 63%, with NVA time of 244.5 minutes and an NNVA time of 471 minutes. In the future state map, the work efficiency becomes 82% due to kaizen improvement, re-layout, and process redesign in the warehouse, with the total NVA become zero and NNVA reduce to 177 minutes.